Avaliação da interação in vitro da Amoxacilina/Clavulanato de Potássio com Isoniazida, Rifampicina, Etambutol e Linezolida contra Mycobacterium tuberculosis - Pagliotto, Aline Daniele Furlan (2013)
The Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis Complex, and M. tuberculosis is, clinically, the most important specie. According to the World Health Organization (WHO), took place in 2011 8.7 million new cases worldwide. The traditional chemotherapy of TB has limitations due resistant strains and the side effects of some drugs. These problems have been exacerbates by outbreaks with multi-resistant strains (MDR-TB). An alternative for the treatment of TB is the association of new compounds with the drugs already used, obtaining synergic effect and consequent decrease of doses. The checkerboard method is used to evaluate the antimicrobial combination and check whether the effect of the drugs combined is significantly greater than the results of drugs used separately.The amoxicillin / clavulanate potassium (AMO / CLAV) has already been studied in some papers, and present an interesting result and suggests further research to better interpretation. Thus, the objective of this study was to evaluate the in vitro antimicrobial activity of AMO / CLAV in combination with the drug isoniazid (INH), rifampicin (RIF), ethambutol (EMB) and linezolid (LINE) against M. tuberculosis and verify the synergistic action of these compounds. In the combination of AMO / CLAV with INH, there was synergism in eight clinical isolates (33.33%). Between RIF and AMO / CLAV there was synergism in nineteen clinical isolates (79.16%). In the interaction with the EMB, there was synergism in reference strain H37Rv and clinical isolates with nineteen (79.16%). Already in association with LINE, there was synergism in just five clinical isolates (20.83%). Our studies show that AMO / CLAV is very promising for future studies in treatment of anti-TB drugs and aid in the treatment of MDR-TB. Similarly to the results of the interaction of AMO / CLAV with anti-TB drugs, their use in combination in treatment could contribute to reducing the dosage of INH, RIF and especially the EMB showing important side effects for the patient.